2008
DOI: 10.1007/s11705-008-0040-1
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of CO2 in solid-state PET measured by pressure-decay method

Abstract: The solubility of CO 2 in solid-state PET was measured using a pressure-decay method. In order to calculate the solubility of CO 2 in the amorphous region of PET, the crystallinity of solid state PET dissolved in CO 2 at different pressures and temperatures was measured by differential scanning calorimetry (DSC). The solubility increases with increasing pressure and it follows a linear relationship and obeys Henry's law when the pressure is below 8 MPa. The effect of temperature on solubility is weak and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The pressure decay method also uses a pressure chamber that includes the polymer sample under gas pressure . The absorbed amount of gas is calculated from pressure decay over time using the ideal gas law or equation like the Benedict–Webb–Rubin equation . Drawbacks of this method are a long measurement time and the need for highly sensitive pressure transducers .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The pressure decay method also uses a pressure chamber that includes the polymer sample under gas pressure . The absorbed amount of gas is calculated from pressure decay over time using the ideal gas law or equation like the Benedict–Webb–Rubin equation . Drawbacks of this method are a long measurement time and the need for highly sensitive pressure transducers .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…4 compares the model prediction and the experimental data for the systems, and it is observed that SL-EoS predicts the experimental data with reasonable accuracy. Furthermore CO 2 solubility in PS has been checked experimentally from high pressure calorimetric analysis to trust the data obtained by the Sánchez and Lacombe model [45,46,51].…”
Section: Solubility Of Co 2 In Polystyrenementioning
confidence: 99%
“…A great number of studies have been published on the swelling and mechanical and physical properties of PET in SC-CO 2 . Chen et al [9] investigated the solubility of CO 2 in solid PET and showed a linear relationship with Henry's law at low pressure (less than 8 MPa), and the solubility decreased with the increase of temperature at high pressure. Chen [10] compared the effects of temperature (50 ∼ 120°C) and pressure (0.1 ∼ 20 MPa) on the swelling rate of PET and obtained the polymer glass transition temperature in the supercritical fluid environment by their self-made high pressure autoclave with a view window, which detected the length change of PET film in the CO 2 state via a CCD camera.…”
Section: Introductionmentioning
confidence: 99%